Factors Affecting Job Stress in Construction Workers - Trie Islamy Pangestu Astid Putera; Tri Martiana (The Indonesian Journal of Occupational Safety and Health, 2022)
Introduction: TIn the 3rd SDGs target is “Ensure Healthy and Promote Wellbeing for all ages", it is hoped that the workforce is not only free from illness but also free from psychological disorders, one of which is job stress. Job stress is a negative impact of a job, especially in dealing with situation and demand that exceed the worker’s ability to cope. Job stress arises because knowledge of workers problem solving not fit with job demand at organization or company. Job stress can degrade workers ability to solve problem. The worker's ability to cope with job stress is not same. Job stress may occur in construction workers whose jobs are monotonous. This study aims to analyze the factors that affect job stress in construction workers. Internal factors include exercise habit and social support. External factors include job demand, work period, and non-work activities. Method: This was observational study which approach by cross-sectional in a construction company. The sample of this study was 55 workers. This study used National Institute Occupational Safety and Health (NIOSH) Generic Job Stress Questionnaire instrument. The variables in this study were internal factors: exercise habit and social support. External factors: job demand, work period and non-work activities. The data were analyzed statistically with the Ordinal Regression Test. Results: Internal factor that have a significant effect was exercise habit variable (p=0.014). External factor that have a significant effect was job demand (p=0.045). Conclusion: Exercise habit can affect the ability of workers to deal job stress. The job demand factor can affect the job stress.Keywords: construction workers, job stress, the SDGs 3rd